(untitled) (Global Journal of Management and Business Research, 2020)
The following is a case study regarding an interoperability experience implemented in Colombia for the development of the land restitution public policy. After an academic review of the concept of interoperability, this document contrasts the different postulates it encompasses with a concrete case implemented in Colombia since 2014. With the help of 12 Colombian State entities, the direct support of the Ministry of Information Technology and Communications and the leadership of the Land Restitution Unit, this experience reflects the complexity,